Tema Yang Muncul Dalam Penerimaan Pajak ( Tinjauan Bibliometrik) - Asesi Winda Yanti Hulu; Fitri Ana; Rachmat Agus Santoso (ITB AAS INDONESIA, 2024)
This research presents a comprehensive review of emerging themes in tax revenue research over the last decades through bibliometric analysis. By checking the number of publications and topic developments in the field. this research identifies emerging trends and shifts in research focus. Using bibliometric methods, this research highlights key themes, influential authors, and important publication venues, providing valuable insight into the trajectory of research on taxation using VOSviewer and Microsoft Excel to conduct frequency analysis of the data. In research findings contribute to a deeper understanding of emerging themes in tax revenue and inform future research directions in this area.